Attribute Preference Stability for Complex Products - Hlédik, Erika (Marketing & Menedzsment, 2019)
The key main focus of our research is understanding consumers’ preference for complex products. First, we describe some different dimensions of product attribute preference investigation as attribute preference measurement methods, preference construction process, type of attributes and stability in term how the product complexity affects these investigations. Then we present the results of an empirical research measuring stability of product preference of complex products using an experiment built into longitudinal survey. In this article the complex product investigated is mobile phone, which has many attributes and characteristics. Finally we discuss empirical and practical consequences, and further research plans.